Republic of Congo : Staff Report for the 2004 Article IV Consultation and a New Staff-Monitored Program. (IMF Staff Country Reports; Country Report ;, 2004)
This paper examines Congo's 2004 Article IV Consultation and New Staff-Monitored Program (SMP). In the context of improved security, the pace of economic activity in the non-oil sector has increased. Non-oil real GDP increased by about 10 percent per year on average during 2000-03. Consumer price inflation decelerated significantly in the postwar period. The fiscal position in 2003 improved from the exceptionally poor performance of 2002, but the underlying fiscal effort was weak relative to the 2003 budget.